Empirical analysis of social exclusion - Matković, Teo; Štulhofer, Aleksandar (2006)
This chapter estimates the extent of multi-dimensional social exclusion in Croatia (based on research data from 2003) and compares the extent of deprivation of included, vulnerable and socially excluded groups, as well as well as socio-demographic and geographical distribution of social exclusion.
Projekt MZOS
ENG